2019
DOI: 10.1098/rsos.190772
|View full text |Cite
|
Sign up to set email alerts
|

Foraging ecology of African wolves ( Canis lupaster ) and its implications for the conservation of Ethiopian wolves ( Canis simensis )

Abstract: African wolves (AWs) are sympatric with endangered Ethiopian wolves (EWs) in parts of their range. Scat analyses have suggested a dietary overlap between AWs and EWs, raising the potential for exploitative competition, and a possible conservation threat to EWs. However, in contrast to that of the well-studied EW, the foraging ecology of AWs remains poorly characterized. Accordingly, we studied the foraging ecology of radio-collared AWs ( n = 11 individuals) at two localities with varyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Hyenas appeared to predate livestock in accordance with its abundance as livestock populations around SSHS are greatest during the wet season (Berhanu 1974). The greater predation of livestock by African wolves during the dry season around SSHS is consistent with the results of research on African wolf diets at Guassa Community Conservation Area, Ethiopia where their biggest dietary focus was on rodents and arthropods, with livestock as a dietary supplement peaking in the dry season (Gutema et al 2019).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Hyenas appeared to predate livestock in accordance with its abundance as livestock populations around SSHS are greatest during the wet season (Berhanu 1974). The greater predation of livestock by African wolves during the dry season around SSHS is consistent with the results of research on African wolf diets at Guassa Community Conservation Area, Ethiopia where their biggest dietary focus was on rodents and arthropods, with livestock as a dietary supplement peaking in the dry season (Gutema et al 2019).…”
Section: Discussionsupporting
confidence: 82%
“…This more even distribution of hyenas can probably be explained by the greater ability of hyenas to exist in varied landscapes via a combination of livestock predation (Kissui 2008, Mbise et al 2018), predation on wild animals (Kissui 2008, Girmay et al 2015) and/or feeding on discarded refuse in human dominated areas (Gidey and Bauer 2010, Yirga et al 2014). Conversely, a recent study in the Guassa Community Conservation Area of northern Ethiopia revealed that livestock accounted for less than 20% of the diet of African wolves, with rodents and arthropods being the biggest contributors (Gutema et al 2019). Moreover, when preying on livestock around SSHS, African wolves focused only on goats and sheep, the livestock of lowest economic value.…”
Section: Discussionmentioning
confidence: 99%
“…Guassa consists of rolling hills, flat plateau areas, cliffs along its eastern border (on which the geladas sleep at night), and farms along its other borders, with one road bisecting the area. (Ashenafi, 2001;Gutema et al, 2019;Lin et al, 2020). During 2007-2012, the mean monthly temperature at Guassa was 11.0 ± 1.2 (SD) °C (Fashing et al, 2014).…”
Section: Study Sitementioning
confidence: 99%
“…The afro-alpine ecosystem is one of the most important ecological regions in sub-Saharan Africa [8]. As a top predator, the Ethiopian wolf control and regulate the function, integrity, and productivity of the ecosystem [9]. Besides, it has a significant role in the national economy being a potential source of tourism attraction [10].…”
Section: Introductionmentioning
confidence: 99%
“…So far, a wide range of studies has been conducted on species biology, ecology, human interaction, and diseases [4,9,11,12,13]. The findings of the previous studies paved the way and set the foundation for the conservation of species and their ecosystem.…”
Section: Introductionmentioning
confidence: 99%